Probabilistic framework for assessing risks to structures stemming from accidental explosions - Vaidogas, Egidijus R. (Journal of Civil Engineering and Management, 2002)
In the paper, an attempt is made to formulate a probabilistic framework for an assessment of risk to structures resulting from accidental vapour cloud explosions (VCEs). This framework is based on the general methodology known in the quantitative risk analysis as the classical Bayesian approach to risk assessment. Attention is centred on the estimation of the annual probabilities of potential damages to structural systems exposed to dangers of VCEs. The paper sets up the mathematical problem of assessing risk to structures related to VCEs and, for the most part, contains discussion on the methodological tasks to be solved in this assessment. Frist Published Online: 30 Jul 2012